2015
DOI: 10.1016/j.msec.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

IR 820 dye encapsulated in polycaprolactone glycol chitosan: Poloxamer blend nanoparticles for photo immunotherapy for breast cancer

Abstract: In the present study, we have fabricated biocompatible and biodegradable monodisperse IR 820 encapsulated polycaprolactone (PCL) glycol chitosan (GC): Poloxamer blend nanoparticles (PP-IR NPs) for imaging and effective photo-immunotherapy. IR 820 has been used as an imaging and photothermal agent whereas glycol chitosan (GC) as an immunostimulatory agent. The combination of IR 820, poloxamer, and GC can be used effectively for photoimmunotherapy for cancer, drug-resistant and TNF-α resistant estrogen positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…[42] Owing to its immunostimulatory effect, glycated chitosan (GC) can be used as both an immunoadjuvant and acarrier to enhance the uptake and presentation of tumor antigens,i ncrease tumor immunogenicity,a nd synergize with PTT.K umar and Srivastava developed biocompatible and biodegradable monodisperse polycaprolactone/GC/Poloxamer blend NPs encapsulating photothermal agent IR 820 for imaging and photo-immunotherapy.Though the NPs enhanced toxicity on MCF-7 cells upon laser treatment, the immune response and efficacyinvivo were not investigated. [43] Angewandte Chemie As ap otent stimulator of the immune system, PTT has also shown synergy with ICB to reverse immunosuppression. Wang et al demonstrated the first combination of anti-CTLA-4 therapy with PTT using single-wall carbon nanotubes.T his stimulated DC maturation in tumor-draining lymph nodes (TDLNs), induced infiltration of effector Tcells, and greatly abrogated Treg cells in non-heated distant tumors, thereby reducing tumor burden in both subcutaneous and lung metastasis models and leading to prolonged survival.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…[42] Owing to its immunostimulatory effect, glycated chitosan (GC) can be used as both an immunoadjuvant and acarrier to enhance the uptake and presentation of tumor antigens,i ncrease tumor immunogenicity,a nd synergize with PTT.K umar and Srivastava developed biocompatible and biodegradable monodisperse polycaprolactone/GC/Poloxamer blend NPs encapsulating photothermal agent IR 820 for imaging and photo-immunotherapy.Though the NPs enhanced toxicity on MCF-7 cells upon laser treatment, the immune response and efficacyinvivo were not investigated. [43] Angewandte Chemie As ap otent stimulator of the immune system, PTT has also shown synergy with ICB to reverse immunosuppression. Wang et al demonstrated the first combination of anti-CTLA-4 therapy with PTT using single-wall carbon nanotubes.T his stimulated DC maturation in tumor-draining lymph nodes (TDLNs), induced infiltration of effector Tcells, and greatly abrogated Treg cells in non-heated distant tumors, thereby reducing tumor burden in both subcutaneous and lung metastasis models and leading to prolonged survival.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…49 This was an exciting finding, but the complexity of this NP formulation may pose a significant barrier to its clinical translation. 21,48,49,51 In this work, we have developed biodegradable, polymeric NPs comprised of poly(lactic-co-glycolic acid) (PLGA) loaded with the NIR-absorbing dye IR820 (IR820-PLGA NPs) to enable proapoptotic PTT of TNBC. 51 They found that PTT mediated by their NPs induced a substantial amount of cell death, but the amount of cell death was only~10% greater than that induced by the NPs without light irradiation, which provide strictly doxorubicin delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is to load PSs into targeted delivery nano‐carriers such as liposomes or polymer nanoparticles . Due to the aggregation‐caused quenching (ACQ) effect, traditional PSs generally show dramatically reduced ROS generation after being encapsulated into nanoparticles, compromising the final therapy performance.…”
Section: Introductionmentioning
confidence: 99%